A Comprehensive Review on the Management of III Nerve Palsy - Anita Ganger; Shikha Yadav; Archita Singh; Rohit Saxena (Delhi Journal of Ophthalmology)
The third cranial nerve is a motor nerve chiefly involved in execution of movements of the eye. The paresis or paralysis of the one or more of these muscles due to oculomotor nerve palsy, leads to ptosis, anisocoria and ocular motility defects. This article highlights the origin and course from nuclear level to terminal branches along with associated clinical symptoms and signs that help in localizing the site of lesion and planning appropriate management.